PELATIHAN SELAM SEBAGAI UPAYA PENGUATAN KAPASITAS KELOMPOK PENGELOLA SASI - Tuapetel, Friesland; Abrahamsz, James; Manuputty, Jan; Ayal, Frederik W.; Makailipessy, Marvin M. (Pattimura University, 2025)
East Seram, Maluku, is one of the regions that still preserves the sasi tradition as a form of local wisdom in managing coastal resources. However, social changes and increasing economic pressures threaten the sustainability of this practice. This community service program aims to strengthen the capacity of sasi management groups through diving training focused on improving knowledge and skills in maintaining and utilizing marine resources sustainably. The training materials covered basic diving techniques, safety, and an introduction to scientific diving to support marine ecotourism and coastal ecosystem monitoring. Evaluation results showed a significant improvement in participants’ understanding and skills related to basic diving principles and underwater conservation. This program contributes to enhancing community competence, strengthening the role of sasi groups, and promoting the development of a sustainable marine ecotourism-based economy